'As o'er the upland hills I take my way': Rural Landscape and the Chronotopes of Memory and Threshold in Ann Yearsley's 'Clifton Hill'. (March 2015) - Markidou, Vassiliki
<x xml:space="preserve">Abstract</x> The article focuses on Ann Yearsley's topographical poem, 'Clifton Hill', in the light of Mikhail Bakhtin's chronotopes of memory and threshold, and demonstrates that the poem alerts its reader to the fact that it is shaped by and reflects the following: first, Yearsley's effort to articulate her deep pain for the loss of her beloved mother; second, the crisis she underwent due to it; and finally her restoration to life through the redemptive power of poetic creation. The essay also argues that in a temporal framework that is not marked by linearity but instead blends past, present, and future, Yearsley employs both prolepsis and analepsis in order to transform the specific rural locality from an ordinary place into a special site, a palimpsest that both shapes and reflects her complex poetic identity. The particular space thus becomes both the place that preserves the memory of Yearsley's precious mother and the springboard for her poetic vocation. In sum, in 'Clifton Hill' Yearsley recollects the past, appreciates the present, and anticipates the future; and, finally, constructs a poem that constitutes a testimony to her ongoing effort to mark her literary achievement and legitimate her authorial agency. In conclusion, the paper evidences that 'Clifton Hill' in its entirety constitutes a threshold marking the borderline between life and death, memory and oblivion, aperture and fatalism, freedom and oppression, openness and closure, the rural and the commercial, and finally, the labouring and upper classes.